PENERAPAN TEKNIK RELAKSASI GENGGAM JARI PADA PASIEN APPENDIKTOMI DENGAN MASALAH GANGGUAN NYERI POST OPERASI - Rahmadhani, Dessy Noor; Purwanti, Okti Sri; Anayanti, Ika Diyah (Poltekkes Kemenkes Bandung, 2025)
Appendicitis is inflammation of the appendix or worm's tuft, in general this infection can cause acute inflammation and therefore requires appendectomy surgery to prevent complications. Pain causes the release of stress hormones and inhibits the healing process, so it is necessary to treat post-appendectomy pain pharmacologically and non-pharmacologically. One non-pharmacological therapy that can be used to treat pain is finger grip relaxation. The study aimed to determine the effectiveness of applying finger grip relaxation in relieving pain in post-appendectomy patients. This case study used one subject with inclusion criteria for post-appendectomy patients who experienced pain and exclusion criteria for post-appendectomy patients who experienced complications who were given interventions from evidence-based nursing, finger-hold relaxation techniques for 15 minutes, each finger for 3 minutes, which were given to post-appendectomy patients. appendectomy with mild to moderate pain as measured using the Numeric Rating Scale (NRS) 0-10. The result showed that after the intervention was carried out for 3 days, the patient's condition improved and the pain was on a scale of 3 compared to the previous scale of 5. Relaxation of holding the fingers was carried out for 15 minutes, one by one the fingers were held for 3 minutes and was carried out for 3 consecutive days and the scale The patient's pain decreased on the third day.